2014
DOI: 10.1007/s10096-014-2277-6
|View full text |Cite
|
Sign up to set email alerts
|

Ecthyma gangrenosum and ecthyma-like lesions: review article

Abstract: The generally accepted definition of ecthyma gangrenosum (EG) states that this condition is pathognomonic of Pseudomonas septicemia (Pseudomonas aeruginosa) and that it should usually be seen in immunocompromised patients, particularly those with underlying malignant disease. The cases described in the literature present a somewhat different picture. Our objective was to analyze this controversy. The review analyzes 167 cases of EG that were described in the literature from 1975 to 2014. All articles on EG cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
198
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 179 publications
(211 citation statements)
references
References 64 publications
5
198
0
8
Order By: Relevance
“…Previously, ecthyma gangrenosum was assumed to be caused solely by P. aeruginosa and that too only in the immunocompromised patients [2].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, ecthyma gangrenosum was assumed to be caused solely by P. aeruginosa and that too only in the immunocompromised patients [2].…”
Section: Discussionmentioning
confidence: 99%
“…Although previously thought to occur primarily due to P. aeruginosa infection, newer studies [2] have revealed the condition to be caused by other bacteria [3,4] and fungi [5,6] too. The lesion starts as an erythematous papule, which slowly evolves to form a haemorrhagic blister, which then deroofs to reveal a characteristic ulcer with dark necrotic eschar and surrounding erythema [1].…”
Section: Introductionmentioning
confidence: 99%
“…Se manifiesta con máculas y pápulas que evolucionan a bulas hemorrá-gicas, que al denudarse, dejan úlceras que evolucionan con necrosis y un halo eritematoso periférico. En dos tercios de los casos las lesiones se localizan en los glúteos y extremidades inferiores 1 . Si bien la mayoría de las veces el EG es causado por Pseudomonas aeruginosa, otros agentes bacterianos, fúngicos e incluso virales se han asociado con esta entidad, planteando desafíos especialmente en el diagnóstico microbiológico y terapia antimicrobiana.…”
Section: Introductionunclassified
“…It is characterized by a gunmetal gray infarcted macule or papule with surrounding erythema, which evolves into a necrotic, black, ulcerative eschar with an erythematous halo. The skin lesions usually appear in the gluteal and perineal regions (57%) or extremities (30%) but could appear anywhere [1]. …”
mentioning
confidence: 99%
“…It is described that 58% of the patients with EG caused by PA suffered from sepsis or bacteremia. It is concluded that EG could also develop as a primary lesion without sepsis and bacteremia, and these patients usually have a better prognosis [1]. …”
mentioning
confidence: 99%